Fundamentals of television production - Donald, Ralph. 4 0 16; Maynard, Riley.;Spann, Thomas; 5 (Boston : Pearson/Allyn and Bacon, 2008)
Presents fundamentals of television production, covering aesthetic considerations, equipment, scriptwriting, production design, and directing, and including word lists and more than five hundred pictures and illustrations.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Production and direction.;Production and direction. -- Television;Television; 20; 2